1980
DOI: 10.1084/jem.151.3.755
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a lymphocyte growth factor by treatment of human cells with neuraminidase and galactose oxidase.

Abstract: The oxidizing mitogens, sodium periodate and galactose oxidase, induce proliferation ofT cells by generation of aldehyde moieties on cell surface glycoproteins (1-3). A brief (30-min) incubation of lymphocytes with these agents is sufficient to generate the mitogenic signal. The oxidizing agent can then easily be removed by washing the cells. These procedures provide a useful tool for investigation of soluble factors that are released from activated lymphocytes and that may play a role in mediating lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Activated T cells have been grown in culture only by the continual addition of IL-2. In all cases, such cell lines have been shown to mediate effector T cell function and have not been found to demonstrate capacity for IL-2 production (7,9,15). The notion that I1-2producing cells die upon factor release is also supported from our previous studies conducted on an IL-2-producing murine T cell lymphoma.…”
Section: Discussionmentioning
confidence: 70%
“…Activated T cells have been grown in culture only by the continual addition of IL-2. In all cases, such cell lines have been shown to mediate effector T cell function and have not been found to demonstrate capacity for IL-2 production (7,9,15). The notion that I1-2producing cells die upon factor release is also supported from our previous studies conducted on an IL-2-producing murine T cell lymphoma.…”
Section: Discussionmentioning
confidence: 70%
“…It should be stressed that an excellent source of mitogen-free IL-2 could be obtained via neuraminidase/galactose oxidase (NaGO) treatment of human peripheral blood cells. Originally described by Novogrodsky and his co-workers (Novogrodsky et al 1980) as a procedure for triggering human T cell proliferation, we have recently found that NaGO treatment of human PBL produces supernates with considerable IL-2 activity.…”
Section: Vl Optimization Of Il-2 Production Proceduresmentioning
confidence: 89%
“…As is clear from examination of the data displayed in Table V, harvest of conditioned medium with peak IL-2 activity was cell concentration and culture duration dependent. This was most likely due to the well documented observation that IL-2 supernate titer depends upon two competing reactions: the first being IL-2 production by a subpopulation of T cells and the second being the binding of IL-2 by a proliferating mitogen-ac- Novogrodsky et al 1980). tivated T cell subset in the same culture (Smith et al 1979a, Bonnard et al 1979, Coutinho et al 1979.…”
Section: Vl Optimization Of Il-2 Production Proceduresmentioning
confidence: 99%